Biocatalytic potential of protease-resistant phytase of Aspergillus oryzae SBS50 in ameliorating food nutrition. (4th May 2015) - Sapna,; Singh, Bijender
Abstract: Production of protease-resistant phytase by Aspergillus oryzae SBS50 was optimized in solid state fermentation using wheat bran as substrate. An integrated statistical optimization approach involving the Placket–Burman design followed by response surface methodology was employed. Among all the variables tested, incubation period, triton X-100, moisture ratio, and magnesium sulphate were identified as significant and further optimized using response surface methodology that resulted in 3.35-fold improvement in phytase production from 55.43 to 185.75 U/g dry mouldy bran (DMB). Optimal conditions for maximum phytase production (185.75 U/g DMB) included wheat bran 10 g per 250 ml flask moistened with 35 ml distilled water supplemented with 3.0% triton X-100, 0.04% magnesium sulphate, 1.0% sucrose and 0.5% yeast extract incubated at 30 °C for an incubation time of 48 h. Phytase titers were sustainable (179.55 to 185.75 U/g DMB), when the mould was grown in shake flasks of varied volumes and enamel-coated metallic trays under optimized conditions. Fermentation time was reduced to half from 96 h to 48 h after optimization resulting in a 6.7-fold enhancement in the phytase productivity from 577.39 to 3868.75 U/Kg/h and thus, reducing the cost of enzyme production. Phytase released inorganic phosphate, reducing sugars and soluble proteins from different food samples in a time dependent manner as a result of phytate hydrolysis.